Pengaruh Profitabilitas, Leverage, Dan Ukuran Perusahaan Terhadap Nilai Perusahaan Pada Perusahaan Subsektor Kosmetik Dan Rumah Tangga Yang Terdaftar Di Bursa Efek Indonesia Periode Tahun 2019-2023 - Sutisna, Nana; Alexander, Alexander; Puspa Rini, Yanti (Universitas Buddhi Dharma/Fakultas Bisnis/Program Studi Akuntansi, 2024)
This study aims to determine the influence of profitability, leverage, and company size on company value. The independent variables used are profitability proxied with ROA and ROE, leverage proxied with DAR and DER, and company size measured by Ln (Total Assets). The dependent variable used is the value of the company as measured by PER. The population of this study is companies in the cosmetics and household subsectors listed on the Indonesia Stock Exchange in 2019-2023. The sampling method used is purposive sampling, samples were obtained from 6 companies with a total of 30 samples for 5 years. The data used is secondary data, namely the company's financial statements on the Indonesia Stock Exchange in 2019-2023. Data analysis techniques used descriptive statistical analysis, classical assumption test, multiple linear regression analysis, determination coefficient test, t-test, and F. Data processing was carried out using the SPSS (Statistical Product and Service Solutions) version 25 program. The data analysis method uses multiple linear regression and for data processing uses SPSS version 24. The results of this study prove that profitability partially has no effect on company value, leverage partially has no effect on company value and company size has an effect on company value. Profitability, leverage, and company size simultaneously have no effect on the company's value.